Strategies to improve interpersonal communication along the continuum of maternal and newborn care: A scoping review and narrative synthesis. - Klaartje M Olde Loohuis; Bregje C de Kok; Winter Bruner; Annemoon Jonker; Emmanuella Salia; Özge Tunçalp; Anayda Portela; Hedieh Mehrtash; Diederick E Grobbee; Emmanuel Srofeneyoh; Kwame Adu-Bonsaffoh; Hannah Brown Amoakoh; et al. (PLOS Global Public Health)
Effective interpersonal communication is essential to provide respectful and quality maternal and newborn care (MNC). This scoping review mapped, categorized, and analysed strategies implemented to improve interpersonal communication within MNC up to 42 days after birth. Twelve bibliographic databases were searched for quantitative and qualitative studies that evaluated interventions to improve interpersonal communication between health workers and women, their partners or newborns' families. Eligible studies were published in English between January 1st 2000 and July 1st 2020. In addition, communication studies in reproduction related domains in sexual and reproductive health and rights were included. Data extracted included study design, study population, and details of the communication intervention. Communication strategies were analysed and categorized based on existing conceptualizations of communication goals and interpersonal communication processes. A total of 138 articles were included. These reported on 128 strategies to improve interpersonal communication and were conducted in Europe and North America (n = 85), Sub-Saharan Africa (n = 12), Australia and New Zealand (n = 10), Central and Southern Asia (n = 9), Latin America and the Caribbean (n = 6), Northern Africa and Western Asia (n = 4) and Eastern and South-Eastern Asia (n = 2). Strategies addressed three communication goals: facilitating exchange of information (n = 97), creating a good interpersonal relationship (n = 57), and/or enabling the inclusion of women and partners in the decision making (n = 41). Two main approaches to strengthen interpersonal communication were identified: training health workers (n = 74) and using tools (n = 63). Narrative analysis of these interventions led to an update of an existing communication framework. The categorization of different forms of interpersonal communication strategy can inform the design, implementation and evaluation of communication improvement strategies. While most interventions focused on information provision, incorporating other communication goals (building a relationship, inclusion of women and partners in decision making) could further improve the experience of care for women, their partners and the families of newborns.